2015
DOI: 10.4331/wjbc.v6.i3.240
|View full text |Cite
|
Sign up to set email alerts
|

Effect of paricalcitol and enalapril on renal inflammation/oxidative stress in atherosclerosis

Abstract: Paricalcitol and enalapril combo treatment ameliorates renal inflammation as well as oxidative stress in atherosclerotic animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…For example, a phenotypic screen of 37 strains of mice22 using the VPR tail‐cuff system (same as in this study) reported a 100±2 to 133±3 mm Hg range of SBPs for those animals. Other laboratories had comparable results using the same39 or different tail‐cuff systems 40, 41, 42. On the other hand, studies that have not concentrated on the tail‐cuff technique show elevated central blood pressure as measured by telemetry during the restraint in mice24, 43 and rats 36, 37, 38.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, a phenotypic screen of 37 strains of mice22 using the VPR tail‐cuff system (same as in this study) reported a 100±2 to 133±3 mm Hg range of SBPs for those animals. Other laboratories had comparable results using the same39 or different tail‐cuff systems 40, 41, 42. On the other hand, studies that have not concentrated on the tail‐cuff technique show elevated central blood pressure as measured by telemetry during the restraint in mice24, 43 and rats 36, 37, 38.…”
Section: Discussionmentioning
confidence: 92%
“…Other laboratories had comparable results using the same 39 or different tail-cuff systems. [40][41][42] On the other hand, studies that have not concentrated on the tail-cuff technique show elevated central blood pressure as measured by telemetry during the restraint in mice 24,43 and rats. [36][37][38] Ours is the first study to show that there is a highly significant difference between simultaneous tail-cuff and central blood pressure telemetry readings.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, combining lisinopril and L-arginine was reported be effective in reversing proteinuria and protecting against renal function impairment in passive Heymann nephritis rats (Zoja et al, 2003). Likewise, in a study by Husain et al (2015), combined treatment of ApoE-knockout mice with paricalcitol and enalapril significantly ameliorated the renal inflammation and oxidative stress.…”
Section: Ace Inhibitors In the Treatment Of Nephritismentioning
confidence: 95%
“…In addition, Husain et al . [21] reported that paricalcitol and enalapril alone or in combination ameliorated the blood pressure and renal lipid peroxidation (LPO), antioxidant defense system and inflammatory proteins in ApoE-deficient atherosclerotic mice; the effect paricalcitol and enalapril in combination was the most potent on renal oxidative stress and antioxidant defense system. Sagar et al .…”
Section: Introductionmentioning
confidence: 99%